The Emperor of Nihon-Ja: Ranger's Apprentice #10 - Flanagan, John (John Anthony) (New York : Philomel Books, 2011)
In a faraway land, a young warrior must protect an emperor from an uprising and train an inexperienced army, with assistance from his Ranger friends.
Keywords: Fantasy; Kings, queens, rulers, etc. -- Fiction